Assessing the Implications of the Covid-19 Pandemic on the Hospitality Sector in Delhi - Choudhury, Kritika; Khullar, Shruti; Bareja, Pallak; Sharma, Paridhi; Singhal, Pavni; Narula, Radhika; Chhabra, Shardul; Poddar, Vanshika; Jha, Shambhavi; Hudda, Ranjeet; Lodhi, Tushar; Arora, Divyanshi; et al. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The hotel management industry in Delhi has been under severe pressure throughout the past year to survive with little to no business. The COVID-19 Pandemic, and the travel restrictions that followed virtually reduced the ambit of the industry to the minimum. In this scenario, various facets of the industry had to employ creative mechanisms to stay afloat. This study focuses on the heavy impacts on various businesses across Delhi, the creative methods adapted to tackle them, and their deliverability. Two separate groups, one of staff working in the management industry in the Delhi NCR region, and another of tourists from and frequently traveling to Delhi were interviewed on the alterations they witnessed, early results of modifications as well as the expected long-term outcomes. New marketing strategies were analysed and an overview of their outcome has been indicated. The introduction of recent liquidity measures and their expected impact have also been highlighted.